Hungary’s castle replicas parks as innovative attractions in cultural tourism - Wirth, Gábor (Studia Mundi – Economica, 2024)
Our castle replicas parks can also play an important role in preserving the history and culture of our country, alongside tourism, which has been growing more and more dynamically in recent years. In reviewing the functions of the model parks, we should highlight the promotion and publicity of the remaining landmarks, as well as the visual transmission of the destroyed built heritage to future generations. The fundamental question of the research is what role model parks play in tourism in Hungary today, and what untapped tourism potential lies in these novel attractions. Following a literature and historical review, both quantitative and qualitative methods were applied in the research. The author used structured qualitative interviews to shed light on the context behind the quantifiable data. The available visitor data, the analysis of the services offered by the model parks and the representation of these facilities in the various development documents were also the subject of the research. When analysing the benefits offered by the model parks, the economic potential of these innovative tourist attractions should not be overlooked, which can be reflected in increased local revenues, a wider range of tourism and services, and job creation, which can also have a positive impact on the image of the municipality or destination, generating additional revenue in the long term. This study was also prepared to fill a gap, as no comprehensive tourism research has been conducted so far on Hungary’s model parks (Mini Skanzen, Castle Replicas Park Dinnyés, Park of a Thousand Years, Hollókő Lego Village, Kisbér Mini Hungary, Magyarkert, Mini Hungary Szarvas and the Mini Castle County Model Park).